2022
DOI: 10.1186/s40008-022-00272-w
|View full text |Cite
|
Sign up to set email alerts
|

Carbon emissions versus value-added in export-driven countries: case of Vietnam

Abstract: Manufacturing for export is gradually becoming the main pillar of economic growth in many developing countries, including Vietnam. Since 1986, Vietnam has adopted an open economic policy and promoted trade activities. Therefore, Vietnam’s exports have significantly increased and contributed to economic development. The benefits of exports are undeniable, but Vietnam also faces serious environmental problems caused by these activities. This paper analyzes the impact of Vietnam’s export activities on economics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…He discussed the sustainability efficiency of Vietnamese firms that care about the green industry; that is, the necessity of reducing CO 2 emissions [6]. Nguyen, P.T., said that carbon emissions decrease with the value added in exports in Vietnam [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…He discussed the sustainability efficiency of Vietnamese firms that care about the green industry; that is, the necessity of reducing CO 2 emissions [6]. Nguyen, P.T., said that carbon emissions decrease with the value added in exports in Vietnam [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nguyen also demonstrated that regional characteristics have an impact on Vietnam's capacity to attract FDI. He just focused on the attraction of FDI inflows in each province in Vietnam [19][20][21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nguyen et al investigated the relationship between financial development and renewable energy in Southeast Asian nations where organic waste materials serve as the primary raw materials. Overall, there is still a research gap regarding the connection between innovation, the consumption of renewable energy, and carbon dioxide emissions in Vietnam [19][20][21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nguyen studied about Carbon Emissions Versus Value-Added in Export-Driven Countries: Case of Vietnam. He noted the more the export of goods and services in Vietnam, the less the CO 2 emission [ 37 ].…”
Section: Literature Reviewmentioning
confidence: 99%